Murals as an element of the tourist image of the city of Odesa - Prykhodko, Z.; Yavorska, L.; Shashero, A.; Nefedova, N.; Molodetskyi, A. (Journal of Education, Health and Sport, 2023)
The article discusses in detail the latest objects of tourist display of the city of Odessa - murals. These works of art increase the aesthetic appeal of the city’s districts, promote cultural heritage and promote the development of tourism in the area, and ultimately, together with other recreational and tourism facilities, influence the formation of the tourist image of the city. Thus, the development and development of excursions with the involvement of a kind of urban art – murals, will contribute to the restoration of tourist activities in the city in peacetime.